STRATEGI PERENCANAAN PEMBANGUNAN DALAM MENGEMBANGKAN POTENSI EKONOMI KOTA PEMATANGSIANTAR PROVINSI SUMATERA UTARA - Nasution, Sri Wahyuni; Wahyuningsih, Yayuk Eko (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
This study aims to look at planning strategies in developing economic potential in Pematangsiantar City, which is in the middle of North Sumatra Province and is the second largest city after Medan City with a distance of more than 128 Km. The entire administrative area is directly surrounded by the administrative area of Simalungun Regency. To review a necessary development plan, a strategy is needed to develop the potential as a source of regional income. The potential that is located in Pematangsiantar City is more conducive to its trade potential. This is due to the adjacent location and as a crossing route to the National Strategic Area (KSN) of Lake Toba, which acts as a supporter in tourism activities. As a city that may be on trade, Pematangsiantar has various historical beauties to visit. However, the main problem that occurs in the potential that exis in Pematangsiantar City consists of many residents living and the lack of natural resources that are utilized in managing their potential resources. a direct knowledge to find out some of the economic potential developed in creating a stable economy in this new normal. Thus we need a research method that uses qualitative and quantitative research, where this research conducts direct interviews from the relevant sources and conducts field observations and also through references that have been carried out by previous research. The results of the research and discussion carried out were obtained from observations from various relevant sources that showed a significant influence between the strategy of its economic potential and the development of its development planning to be stable. Based on several summary tables, it is known that it affects the population and the rate of growth of development infrastructure in Pematangsiantar City. In the end, entering the new normal requires a planning strategy to achieve stable and prosperous development